Tanggapan Masyarakat Terhadap Pelayanan Pembayaran Air PDAM Tirta Daroy Banda Aceh - Ihsanuddin Ihsanuddin (Jurnal EMT KITA, 2017)
This study was conducted to examine the community's response to the water bill payment services at PDAM Tirta Daroy Banda Aceh. The study population was the whole community who pay water bills on PDAM Tirta. Daroy Banda Aceh, amounting to 16 886 people. Given the population is too many, the authors take a few samples. Sample was conducted with a random technique (simple random sampling) without regard to strata that exist in the population so that the population is homogeneous. This study uses independent variable responsiveness, empathy, reliability assurance and keterwujudan community feedback while the dependent variable in the payment of water bills on PDAM Tirta Daroy Banda Aceh. Based on the five variables studied, turned out to have a responsive variable penganih dominant to the public response in the payment of water bills on PDAM Tirta Daroy Banda Aceh followed by a variable empathy, reliability assurance and multiple linear regression keterwujudan.Hasil obtained the explanation that all independent variables studied had a correlation coefficient (relations) close and positive and have determination (influence) a strong and positive impact on the public response in the payment of water bills on PDAM Tirta Daroy Banda Aceh.